Pengembangan Aplikasi Berbasis Web untuk Skrining Tingkat Depresi Ibu Pasca Melahirkan Menggunakan Skala EPDS dan PHQ-9 - Pangestu, Primanita; Widowati, Henny; Pernadi, Dody (Jurnal Ilmiah Informatika Komputer, 2025)
Anxiety and depression are mental health issues that are common in mothers during pregnancy and after childbirth. The prevalence of anxiety and depression among pregnant women is 12.6%, and among postpartum women, it is 10.1%. However, mental health screening is still not an integral part of comprehensive antenatal or postnatal care. This research aims to develop a website-based application for screening postpartum maternal depression levels using the EPDS and PHQ-9 scales. The method used involves application development using the PHP programming language and implementing the EPDS and PHQ-9 scales as assessment instruments. The research findings are a screening application that can help postpartum mothers self-assess their level of depression. The website has been successfully implemented and can be accessed online via the link https://postnatalcare.my.id/. The application is expected to serve as a screening tool for determining the level of postpartum depression in mothers and to assist midwives in monitoring patients' mental health conditions, enabling them to provide appropriate care.